Abundance of liana species in an Amazonian forest of Brazil reflects neither adventitious root nor foliar sprout production. (26th July 2018) - Piovesan, Paulo Ricardo Rodrigues; Camargo, José Luís Campana; Burnham, Robyn Jeanette; Ferraz, Isolde Dorothea Kossmann
Abstract: Liana abundance and size have increased in neotropical forests. High vegetative reproductive capacity (clonality) may be the cause of high abundance in some liana species. Correlations between vegetative propagation capacity and (1) relative abundance of liana species, (2) rooting and foliar sprouting potentials of congeneric species, and (3) phylogenetic position were determined. Species selection was based on the relative abundance of lianas in ten 0.5-ha parcels in continuous forest within the Biological Dynamics of Forest Fragments Project (BDFFP), Brazil. Five individuals per species were replicated with seven cuttings per individual. Cuttings placed in moistened sand and coconut fibre were observed for 5 mo in a humid greenhouse. Survival percentage, rooting percentage, potential regeneration index and longest root length were determined per species. The two most abundant species (9.3% and 4.1% relative abundance) had low vegetative regeneration capacity, contrary to expectations. However, a significant, positive relationship between vegetative propagation and relative abundance of liana species whose relative abundances were <4% was found. Congeneric species showed no difference in vegetative propagation between rare and abundant species, except congeners of Machaerium . Vegetative reproductive capacity occurred in all major evolutionary lineages, but was highest in Fabaceae and Bignoniaceae, families of high abundance both locally and broadly across Neotropical forests.